Analyze Lexicological and Lexicography Example Sentences in Raissa Anggiani Songs - Amelia Christianti Hutagaol (MATCHA: Journal of Modern Approaches to Communication, Humanities, and Academia, 2025)
This research focuses on the interpretation and use of various forms and symbols in music and aims to understand the structure, meaning and use of words in language. This research contributes to the understanding of the relationship between language, music and culture through the analysis of speech and music samples. The research method involves systematically collecting, analyzing and interpreting data using web mining and albums. The method used in this research is a descriptive method that uses a qualitative approach. Data analysis used a methodology to identify and classify data based on its content. This methodology uses lexicography to identify and classify words into lists, and then uses the data as teaching materials, categorizing them by usage, occupation, or status. This research emphasizes the importance of using various forms and symbols in linguistic expression and stresses the importance of using various symbols to effectively convey meaning and emotion.